The crystal structure of trandolapril, C24H34N2O5: an example of the utility of raw data deposition in the powder diffraction file. Issue 3 (September 2016) - Reid, Joel W.; Kaduk, James A.; Vickers, Martin
Abstract : The crystal structure of trandolapril has been solved by parallel tempering using the FOX software package with laboratory powder diffraction data submitted to and published in the Powder Diffraction File. Rietveld refinement was performed with the software package GSAS yielding orthorhombic lattice parameters of a = 19.7685(4), b = 15.0697(4), and c = 7.6704(2) Å (C24 H34 N2 O5, Z = 4, space group P 21 21 21 ). The Rietveld refinement results were compared with density functional theory (DFT) calculations performed with CRYSTAL14. While the structures are similar, discrepancies are observed in the configuration of the octahydroindole ring between the Rietveld and DFT structures, suggesting the refined and calculated molecules are diastereomers.